The Social Weather Reports of economic well-being in the Philippines - Mangahas, Mahar (2018)
Social Weather Stations (SWS) is a private, non-profit, and non-partisan research institute that regularly conducts scientific surveys on various social, economic, and political dimensions of the quality of life of the Filipino people. Its Social Weather Reports stem from a series of nationally representative surveys which were semi-annual in 1986-1991 and have been quarterly since 1992. The Social Weather Reports represent the enlightenment approach to the application of social indicators in a democratic setting. Their indicators of economic well-being include self-rated poverty (SRP), self-rated food poverty, and hunger, measured at the household level. In terms of data points, the quarterly SRP statistics are 12 times as many as the official poverty statistics, which apply monetary poverty lines to triennial surveys of family income. The incidences of SRP are invariably much larger than those of official poverty, which use unrealistically low poverty lines when compared to self-rated thresholds for poverty and food poverty. The time trends of SRP are compatible with official poverty, when matched contemporaneously. They show significant volatility in poverty, not only year to year, but also quarter to quarter. Aside from economic deprivation of households, the Social Weather Reports include the subjective assessments of adults as to whether they have gained or lost in personal quality of life in the past and whether they are optimistic or pessimistic about it for the future. Despite steady growth in per capita Gross National Income, losers regularly outnumbered gainers for decades, but gainers have been dominant since 2014. The Social Weather Reports amply demonstrate that survey-based subjective indicators are more practical and realistic means of monitoring economic well-being than orthodox economic indicators stemming from the National Income Accounts.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 54-55).
Keywords: Social Weather Stations (SWS).; Social indicators; Economic indicators